Medical Students and Faculty Perceptions About Online Learning During COVID-19 Pandemic: Alfaisal University Experience - Arain, Shoukat Ali; Ali, Mahnoor; Arbili, Lana; Ikram, Muhammad Faisal; Kashir, Junaid; Omair, Aamir; Meo, Sultan Ayoub (Frontiers in Public Health, 2022)
Background and Objectives: Off-campus online learning methods abruptly increased and gained popularity during the COVID‐19 pandemic. Previous studies have highlighted the limitations of online learning mode; however, further studies on the experiences of medical students are needed. This study aimed to investigate the preclinical medical students and faculty members' experiences with online education and learning. Subjects and Methods: In this cross-sectional study, data were collected using convenience sampling. Two hundred nine students and 13 faculty members who participated in the online courses offered during the spring semester of 2019-2020 completed an online questionnaire. A 30-item questionnaire for the students and a 25-item questionnaire for the faculty were used in this cross-sectional study. Results: Overall, 30% of the student sample was satisfied; importantly, high-achieving students (GPA > 3.5) were less satisfied (25% vs. 32%; p = 0.006). Satisfaction was also low (35%) for student-faculty interaction opportunities. About half of the student sample agreed that small-group interactive sessions would improve learning (53%). The most favored course format was the blended mode (43%), followed by traditional (40%) and online modes (17%). Six out of 13 (46%) faculty members were satisfied with their online experiences. Most of them found virtual teaching applications convenient (77%). Conversely, few faculty members agreed to interact effectively (54%), while 69% favored a blended format. Conclusions: The level of satisfaction in fully online courses offered during the COVID-19 pandemic remained low, especially among high-achieving students. Both students and faculty favored the blended format for future purposes. Small group active-learning strategies and web-based interactive tools may facilitate engagement and student-faculty interactions.